Adapting to climate change-induced flooding: insights from women traders in the riverine areas of Nigeria—a qualitative study - Michael, Turnwait Otu (Frontiers in Sustainability, 2024)
In the riverine areas of Bayelsa State, Nigeria, the intersection of climate change and flooding poses an escalating threat to the livelihoods and well-being of women traders. This qualitative study investigates the experiences and adaptive strategies employed by women traders in response to climate change-induced flooding. Employing an exploratory research design with purposive sampling, 46 women traders participated in the study, involving 23 indepth interviews and three focus group discussions. Thematic analysis was applied to scrutinize the collected data. The study unravels the impacts of climate change-induced flooding on economic, social, and gender dynamics, revealing economic disparities, gender inequality, livelihood disruptions, inadequate infrastructure, and limited access to information among women traders. Vulnerabilities emanated from disruptions in supply chains, damage to goods, and constrained market access, with agricultural traders being notably affected. Flood events exacerbated gender inequalities, amplifying caregiving responsibilities and limiting decisionmaking power for women traders. Resilience surfaced through diversified income sources, community solidarity, collective narratives, and local adaptive strategies, including indigenous knowledge and innovations. Policymakers and stakeholders should prioritize resilient infrastructure investments, such as flood-resistant marketplaces and storage facilities, to safeguard women traders' businesses during flooding events and enhance the overall economic resilience of the community.